Development of a new food preservation and packaging technique FPR liquid food products by using pyramid shape power - Abdelsamie, Maher Abdelaleem Abdelrazik; Abdul Rahman, Russly; Mustafa, Shuhaimi; Hashim, Dzulkifly; Ab Rahman, Suhaimi (Faculty of Engineering, Universiti Putra Malaysia, 2012)
There is a high demand for packaged, preserved food worldwide especially nowadays due to the rapid growth of the world population to store food for long periods of time, to use off-season and to export to different areas of the world undergoing shortages. Most current preservation techniques cause a reduction in quality and a loss of vitamins and nutrients, therefore a top priority in food sciences has been the elucidation of alternative, less stringent techniques. The Pyramid shape technique combines preservation and packaging in one process and is poised to be a useful tool to the food industry. The Pyramid shape technique creates a unique opportunity for both food manufacturers and consumers to package, preserve and produce a new kind of structured water that has many beneficial effects for human health. The new technique, based on the mystery of the dimensional ratio of the Great Pyramid of Giza in Egypt, it is the only responsible factor for the water molecular structure alteration and the preservation effect without any other physical or chemical treatment. The effects of pyramidal and square packaging shapes on mineral water were studied by examining ice surface morphology. Ice surface morphology was examined by variable pressure scanning electron microscopy VP-SEM. The pyramid shaped container promotes the formation of filament shaped water and mineral particles. These results provide evidence that a pyramidal container acts to structure water in an ordered manner.